Pengaruh Gel Ekstrak dan Serbuk Mentimun (Cucumis sativus) terhadap Angiogenesis pada Penyembuhan Luka Bakar Derajat IIB pada Tikus Wistar (The Effect of Cucumber (Cucumis sativus) Gel Extract and Powder on Angiogenesis of the IIB Degree-Burn Wound He - Ardhina Mahadica Nugroho; Ulfa Elfiah; Rena Normasari (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Burns is a serious global health problem. Annually, 265.000 dead occured because of burns. Local burns wound treatment ideally uses material that can act as antimicrobial and antiinflamation, as well conditions moist environtment. Cucumber contains flavonoid and saponin that enhance Vascular Endothelial Growth Factor that can increase angiogenesis. The purpose of this research was to investigate the effect of cucumber extract gel and cucumber powder gel on number of vascular lumen angiogenesis of IIB-burn wound healing in wistar rat. This research was true experimental laboratories with post test control only design by using wistar rats and divided into 8 groups. Rats were burns-induced and then terminated on the 3rd and the 10th day, each group consist of negative control group (normal saline), positive control group (gentamycin eye ointment), treatment group 1 (cucumber extract gel), treatment group 2 (cucumber powder gel). Data analysis using One Way ANOVA test for the 3rd day and the 10th day on vascular lumen number showed 0,031 and 0,036 (p<0,05) significance respectively. In conclusion, there was significant difference for cucumber extract gel and cucumber powder gel towards vascular lumen number in IIB-burns wound healing in wistar rat. Keywords: Burns, wound healing, angiogenesis, cucumber (Cucumis sativus)